2015
DOI: 10.2166/washdev.2015.103
|View full text |Cite
|
Sign up to set email alerts
|

Effect of hydraulic loading on the performance of unplanted drying beds treating low-concentrated faecal sludge

Abstract: To optimize faecal sludge (FS) treatment plants in operation in Dakar (Senegal), this study was conducted to test the effectiveness of the solid/liquid separation on unplanted drying beds under different loading rates and two operation strategies (one or two feedings per campaign). Clogging, purification performances, dryness and hygienic quality were monitored. Results have shown that the load fractionation has reduced the clogging. Only removals of total solids (TS) and slightly those of total Kjeldahl nitro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Several operational variables and design factors have been found to affect the reduction of helminth eggs in VFCW. Indeed, Sonko et al (2015) pointed out the reduction of helminth eggs in FS to be affected by hydraulic loading. Manga et al (2016) revealed the effect of sand filter media thickness on the removal performance of helminth eggs in FS drying beds.…”
Section: Introductionmentioning
confidence: 99%
“…Several operational variables and design factors have been found to affect the reduction of helminth eggs in VFCW. Indeed, Sonko et al (2015) pointed out the reduction of helminth eggs in FS to be affected by hydraulic loading. Manga et al (2016) revealed the effect of sand filter media thickness on the removal performance of helminth eggs in FS drying beds.…”
Section: Introductionmentioning
confidence: 99%